Efektivitas Kegiatan Seni Hadroh Sebagai Media Dakwah dalam Pembinaan Akhlak Remaja Desa Terentang Bangka Barat - Amelia Saputri; Gela Lestari; Iqbal Iqbal; Madani Cahya Prasasti; Navita Hasybyah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The most famous Islamic art in Indonesia is Hadrah. Hadrah art is a medium of da'wah for the moral development of adolescents. It is during these adolescent phases that it is the most appropriate and longest phase to instill principles and correct guidance on adolescent behavior. The purpose of this study was to determine the effectiveness of hadroh art activities as a medium of da'wah in developing adolescent morals. The type of research used in this research is field research which will be carried out in Terentang Village, West Bangka Regency. While the approach used is a qualitative approach with a qualitative descriptive method, namely a research method that aims to fully and in-depth describe social reality and various phenomena that occur in society which are the subject of research so that the characteristics, characteristics, characteristics and models of the phenomenon are described. This hadrah art activity is included in the da'wah media in instilling Islamic moral values, so this activity is effective in fostering the morals of Terentang village youth.